2014
DOI: 10.1037/a0036572
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Short Mood and Feelings Questionnaire in late adolescence.

Abstract: Studies examining the validity of the Short Mood and Feelings Questionnaire (SMFQ; Angold, Costello, & Messer, 1995) have largely focused on selected or clinical samples in childhood (6-11 years) or early to midadolescence (12-16 years) and have not investigated misclassifications or how the SMFQ relates to adult depression measures. Using data from the Avon Longitudinal Study of Parents and Children (2012), we assessed the validity of the SMFQ in relation to an adult depression measure administered in late ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
174
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 47 publications
(78 reference statements)
6
174
1
Order By: Relevance
“…The SMFQ consists of 13 statements (eg, ‘I am feeling low’, ‘no one likes me’ and so on) that the participants respond to using Norwegian translations of the response categories ‘not true’, ‘sometimes true’ and ‘true’. The SMFQ is a valid instrument48 with adequate psychometric properties,49 and a previous study based on the youth@hordaland study found the SMFQ to be unidimensional, supporting the use of the sum score of SMFQ 50. Reliability in the current sample was excellent (range=0–26, ordinal α=0.95).…”
Section: Methodssupporting
confidence: 66%
“…The SMFQ consists of 13 statements (eg, ‘I am feeling low’, ‘no one likes me’ and so on) that the participants respond to using Norwegian translations of the response categories ‘not true’, ‘sometimes true’ and ‘true’. The SMFQ is a valid instrument48 with adequate psychometric properties,49 and a previous study based on the youth@hordaland study found the SMFQ to be unidimensional, supporting the use of the sum score of SMFQ 50. Reliability in the current sample was excellent (range=0–26, ordinal α=0.95).…”
Section: Methodssupporting
confidence: 66%
“…This threshold has high sensitivity, specificity, and negative predictive power for a diagnosis of depression (according to the International Classification of Diseases, 10th Revision) at age 18 years in the ALSPAC cohort. 28 …”
Section: Psychological Problemsmentioning
confidence: 99%
“…While this measure was originally designed for use with children, it has been validated in older adolescents/young adults. 26 Of note, none of the items in the depression scale measured sleep. One item, "I felt so tired I just sat around and did nothing" tapped fatigue, which could be related to a plethora of different conditions including depression, diabetes, or anemia.…”
Section: Depressionmentioning
confidence: 99%